2006
DOI: 10.1093/ndt/gfk093
|View full text |Cite
|
Sign up to set email alerts
|

On-line haemodiafiltration with and without acetate

Abstract: Background. In patients on on-line convective treatments, given the considerable quantity of dialysis fluid re-infused, the small amount of acetate present in bicarbonate dialysis fluid as a pH stabilizing factor may allow a significant transfer of that anion to the patient, possibly inducing cytokine activation. Methods. To verify this hypothesis, we performed on-line haemodiafiltration (OL-HDF) with (3 mmol/l) and without acetate in dialysis fluid in a cross-over randomized order on 12 prevalent patients. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 19 publications
(23 reference statements)
3
26
1
2
Order By: Relevance
“…However, although the acetate level is typically low, the small amount that the bicarbonate dialysis fluid contains can induce, by itself, an inflammatory stimulus caused by the high volume reinfused to the patient [12]. …”
Section: Introductionmentioning
confidence: 99%
“…However, although the acetate level is typically low, the small amount that the bicarbonate dialysis fluid contains can induce, by itself, an inflammatory stimulus caused by the high volume reinfused to the patient [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, components such as acetate, small quantities of which (approx. 3–5 m M ) are normally present as stabilizing agents in DS and RS produced on-line, may negatively affect erythropoiesis, triggering the inflammatory cascade during the dialysis session [14,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…A challenge test using a commercially available acetic acid showed that serum acetate level was increased to 800 lM during an attack of asthma due to acetate ingestion [1]. In this case, the bicarbonate dialysate contained almost 3-time higher amount of acetate (9.1 mM) compared to the previous ones [5,6]. It is, therefore, likely that a greater load of acetate to the patient during pre-dilution OL-HDF may trigger hypersensitivity reactions to acetate in this case.…”
Section: Discussionmentioning
confidence: 95%
“…It is reported that pre-dilution OL-HDF with 40 L of filtered bicarbonate dialysate containing 3 mM of acetate resulted in an increase of plasma acetate level by about 10-fold (from 25 ± 2 to 316 ± 14 lM), whereas the plasma level of acetate remain in the normal range (1-100 lM) (from 33 ± 5 to 71 ± 15 lM) when using acetate-free dialysate [6]. A challenge test using a commercially available acetic acid showed that serum acetate level was increased to 800 lM during an attack of asthma due to acetate ingestion [1].…”
Section: Discussionmentioning
confidence: 99%